Masthead - Regina Hoffman (Patient Safety)
As the journal of the Patient Safety Authority, committed to the vision of “safe healthcare for all patients," Patient Safety (ISSN 2689-0143) is fully open access and highlights original research, advanced analytics, and hot topics in healthcare. The mission of this publication is to inform and advise clinicians, administrators, and patients on preventing harm and improving safety, by providing evidence-based, original research; editorials addressing current and sometimes controversial topics; and analyses from one of the world’s largest adverse event reporting databases. We invite you to submit manuscripts that align with our mission. We’re particularly looking for well-written original research articles, reviews, commentaries, case studies, data analyses, quality improvement studies, or other manuscripts that will advance patient safety.All articles are published under the Creative Commons Attribution – Noncommercial license, unless otherwise noted. The current issue is available at patientsafetyj.com. The patient is central to everything we do. Patient Safety complies with the Patients Included™ journal charter, which requires at least two patient members on the editorial board; regular publication of editorials, reviews, or research articles authored by patients; and peer review by patients.This publication is disseminated quarterly by email at no cost to the subscriber. To subscribe, go to patientsafetyj.com.Articles accepted for publication do not necessarily reflect practices or opinions endorsed by the Patient Safety Authority.